Afghanistan's Islam : From Conversion to the Taliban - Green, Nile (Book collections on Project MUSE., 2016)
"This book provides the first ever overview of the history and development of Islam in Afghanistan. It covers every era from the conversion of Afghanistan through the medieval and early modern periods to the present day. Based on primary sources in Arabic, Persian, Pashto, Urdu and Uzbek, its depth and scope of coverage is unrivalled by any existing publication on Afghanistan. As well as state-sponsored religion, the chapters cover such issues as the rise of Sufism, Sharia, women's religiosity, transnational Islamism and the Taliban. Islam has been one of the most influential social and political forces in Afghan history. Providing idioms and organizations for both anti-state and anti-foreign mobilization, Islam has proven to be a vital socio-political resource in modern Afghanistan. Even as it has been deployed as the national cement of a multi-ethnic 'Emirate' and then 'Islamic Republic, ' Islam has been no less a destabilizing force in dividing Afghan society. Yet despite the universal scholarly recognition of the centrality of Islam to Afghan history, its developmental trajectories have received relatively little sustained attention outside monographs and essays devoted to particular moments or movements. To help develop a more comprehensive, comparative and developmental picture of Afghanistan's Islam from the eighth century to the present, this edited volume brings together specialists on different periods, regions and languages. Each chapter forms a case study 'snapshot' of the Islamic beliefs, practices, institutions and authorities of a particular time and place in Afghanistan"--Provided by publisher